FRAUD PREVENTION STRATEGIES IN INDONESIAN MSMEs: THE SIGNIFICANCE OF HONESTY AND INTERNAL CONTROL FACTORS - Dwi Rahayu; Rudy Hartanto; Iis Rohayati; Reni Harni (Jurnal Akuntansi, Keuangan, Perpajakan dan Tata Kelola Perusahaan, 2024)
This study highlights the role of honesty and internal control in preventing fraud in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. MSMEs are an important pillar in the national economy, but face challenges such as poor management, limited human resources, and fraud. This study examines the impact of a culture of honesty and the implementation of effective internal controls to reduce fraud risk. The sample consisted of 150 MSMEs. Testing was performed using SmartPLS. The results show that honesty and good internal control can increase the reliability of financial information, operational efficiency, and consumer trust. In addition, the implementation of internal control, which includes risk assessment, control activities, and information and communication, has proven to be effective in mitigating the risk of fraud. To support MSMEs in moving up in class and achieving sustainable success, the government and other stakeholders must provide management guidance, training, and support programs that focus on increasing honesty and internal control. Thus, MSMEs can be better prepared to face business challenges, reduce the risk of fraud, and contribute more to national economic growth. Keywords: Fraud, Honesty, Internal Control, Micro Small and Medium Enterprises, MSMEs